2005
DOI: 10.1126/science.1110265
|View full text |Cite
|
Sign up to set email alerts
|

The Optical Resonances in Carbon Nanotubes Arise from Excitons

Abstract: Optical transitions in carbon nanotubes are of central importance for nanotube characterization. They also provide insight into the nature of excited states in these one-dimensional systems. Recent work suggests that light absorption produces strongly correlated electron-hole states in the form of excitons. However, it has been difficult to rule out a simpler model in which resonances arise from the van Hove singularities associated with the one-dimensional band [corrected] structure of the nanotubes. Here, tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

78
1,205
2
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,181 publications
(1,288 citation statements)
references
References 36 publications
78
1,205
2
3
Order By: Relevance
“…All these phenomena are typical features of quasi-one-dimensional materials 20 such as conjugated organic 21 and organometallic 22 polymers, and mix-valence chains 23 . In particular, recent studies reveal many common electronic features observed in spectra of CNTs and conjugated polymers 7,9,13,24,25 . Figure 1 schematically shows the essential electronic states contributing to photophysics of these materials providing common comparison baseline.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…All these phenomena are typical features of quasi-one-dimensional materials 20 such as conjugated organic 21 and organometallic 22 polymers, and mix-valence chains 23 . In particular, recent studies reveal many common electronic features observed in spectra of CNTs and conjugated polymers 7,9,13,24,25 . Figure 1 schematically shows the essential electronic states contributing to photophysics of these materials providing common comparison baseline.…”
mentioning
confidence: 99%
“…So far, extensive amount of work in nanotube science has been done on the excitonic properties of the singlet manifold only 4,5,6,7,8,9,10,11,12 . Triplet states in CNTs have not been detected experimentally yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Photoluminescence (PL) of nanotubes results from exciton recombination and occurs in the near-infrared spectral range with emission energies controlled mainly by the nanotube structure (n,m). [4][5][6][7][8] Since nanotubes consist of surface atoms only, the detected emission energy is very sensitive to the nanotube environment, making them promising candidates for sensing applications. 9 At present, the influence of the environment is described by its relative dielectric constant ε influencing exciton binding energies but also renormalizing the band gap through charge carrier screening.…”
mentioning
confidence: 99%
“…We found a strong red shift caused by DNA-wrapping of between 7 and 17 meV depending on the nanotube chirality. In the next step, TENOM was used to resolve PL variations along DNA-wrapped (6,5) and (6,4) nanotubes. Here two distinct emission bands are identified and assigned to emission from DNA-wrapped segments of the nanotube at E DNA and unwrapped segments at E 0 , distinguished by energy shifts of 18 meV for (6,5) and 30 meV for (6,4)-nanotubes, respectively.…”
mentioning
confidence: 99%